Analisis Struktur Kekuatan Persaingan Dan Klaster Industri - Erlangga Samudera Utomo; Ratna Sari Julaeha; Muhammad Yasin (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
In the development of the economy, the State of Indonesia experienced a change in the structure of the economy from an agricultural basis to an industrial one, which resulted in many benefits from these changes. The industrial sector has a close relationship with the economy of a country because the progress of the industrial sector is an indicator of the success of a country's economy. Descriptive methods are used to analyze physical and social phenomena and the readiness of an area to become a cluster. The analysis reveals that cluster policies are implemented by national and regional cluster programs. It was also determined that an important element of the cluster policy is the identification of sources of finance and the people responsible for implementing the program. The instrument can be applied by cluster policy actors which are defined in a broad sense, namely business, associations, government actors. In the industrial world, there are five industrial forces in determining the competition of an industry. The method used to determine the strength of the industry based on external factors of the company.